Saddle Strength Analysis on Jacket Structure During Roll Up Procedures in Fabrication Phase - Handayanu Handayanu; Nur Syahroni; Nabila Defriana (International Journal of Offshore and Coastal Engineering, 2022)
Offshore platform is a structure that serves as a well drilling facility to explore, extract, store and process petroleum and gas located under the seabed. There are several phases in theconstruction of offshore structures (fixed jacket platform) from preparation to construction. Fabrication phase is the earliest stage in the manufacture of a fixed offshore platform (jacketstructure) which is carried out by the fabricator. One of the procedures at the fabrication phase is roll up procedure. In this final project research, an analysis will be carried out regarding the configuration of the rigging, crane, and sadle support used in the jacket structure during roll up procedure. After the analysis of jacket structure modeling using the SACS software, the results of rigging configuration can be obtained, which were the slingsspesifications used to connect the structure with cranes, with sling diameter of 2.75 inch and SWL value of 64 MT. As for the sling used to connect the jacket with winch has a diameter of 1.5 inch snd SWL value of 18 MT. Furthermore, the cranes used have a capacity of 75 and 78 MT, respectively. In the load analysis of the jacket structure, it was found that saddle support received the largest reaction when the jacket was at an 80-degree slope with the largest reaction value of 102.74 MT. In the saddle support local analysis, the result of maximum equivalent von-mises stress obtained was 43,486 MPa, with the saddle allowable stress of 345 Mpa, therefore the UC value of 0.24 can be obtained.